Characteristics of cardiac involvement in immune-mediated necrotizing myopathy - Liu, Mengyang; Lin, Ying; Qiao, Lingya; Chen, Juan; Shi, Qiang (Frontiers in Immunology, 2023)
Objective To investigate the characteristics of cardiac involvement due to Immune-mediated Necrotizing Myopathy (IMNM). Methods Patients diagnosed with Immune-mediated Necrotizing Myopathy (IMNM) who attended the Department of Neurology and the Department of Rheumatology and Immunology at the First Medical Center of the PLA General Hospital between February 2011 and June 2022 were collected. Clinicopathological diagnosis of IMNM was performed according to the criteria established by the European Neuromuscular Center (ENMC). All patients underwent muscle biopsy and Myositis-specific antibodies (MSAs) testing. Information included age, gender, disease duration, intramuscular and extramuscular manifestations, laboratory findings (including creatine kinase, lactate dehydrogenase levels, troponin T, myoglobin and atrial natriuretic peptide), electromyography, skeletal muscle pathology and immunohistochemical staining. Results A total of 57 patients were included in this study. Of the serological tests, 56.1% (32/57) were positive for SRP, 21.1% (12/57) were positive for HMGCR and 22.8% (13/57) were seronegative. Thirty patients (52.6%, 30/57) presented with varying degrees of cardiac involvement. We performed ECG in 23 patients and found 6 patients with arrhythmia (26.1%), 12 patients with myocardial ischemia (52.2%), and 7 patients with acute coronary syndrome (ST elevation and non-ST elevation myocardial infarction) (30.4%), and 4 patients with left axis deviation or left ventricular high voltage, suggesting left ventricular hypertrophy (17.4%). Cardiac ultrasound was performed in 14 patients and 3 showed pericardial effusion (21.4%); Decreased left ventricular ejection fraction and atrial enlargement were 2 each; 8 showed a decrease in left ventricular diastolic function (57.1%). In addition, one patient had myocardial edema. Conclusion Cardiac involvement is not uncommon in IMNM. However, besides clearly statistically significant differences in the disease course, and in the values of troponin T and myoglobin, our data did not show any statistically significant difference in other features of cardiac involvement between patients with different subtypes of IMNM.